2009
DOI: 10.5794/jjoms.55.585
|View full text |Cite
|
Sign up to set email alerts
|

A case of carcinoma of the lower lip with superior vena cava syndrome due to secondary mediastinal lymph node metastasis

Abstract: We report a case of carcinoma of the lower lip with superior vena cava syndrome(SVCS)due to secondary metastasis to the mediastinal lymph nodes. The patient, a 77 year-old woman, was referred to our department to treat a tumor in the right side of the lower lip. Histologic examination of a biopsy specimen revealed a well-differentiated squamouse cell carcinoma. The tumor was abraded by en bloc excision surgery with bilateral neck dissection under general anesthesia. Further histological evaluation of an excise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Radiation therapy has long been considered a mainstay of SVCS treatment [4]. Some hospitals [1,2] reported that radiation therapy could be effective in cases in which the symptoms needed to be relieved urgently when the general condition was poor, as in our case. Straka C, et al [4] described that hypo-fractionated RT had the potential to be a more convenient therapy for patients and may provide equal or superior control of underlying malignancies.…”
Section: Journal Of Clinical Case Studiesmentioning
confidence: 62%
See 4 more Smart Citations
“…Radiation therapy has long been considered a mainstay of SVCS treatment [4]. Some hospitals [1,2] reported that radiation therapy could be effective in cases in which the symptoms needed to be relieved urgently when the general condition was poor, as in our case. Straka C, et al [4] described that hypo-fractionated RT had the potential to be a more convenient therapy for patients and may provide equal or superior control of underlying malignancies.…”
Section: Journal Of Clinical Case Studiesmentioning
confidence: 62%
“…CT and MRI studies are commonly used in the initial evaluation of SVCS and can reveal SVC blockage prior to the development of symptoms. After cancer treatment and when following patients with cancercarrier conditions, it is necessary to keep in mind the possibility of SVCS due to longitudinal lymph node metastasis, as well as chest and mediastinum tumors if rapid facial edema appears [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations